Structural properties of nanoscopic ring systems and their optical response - Oliveira Neto, Vivaldo Lopes (Universidade Federal de São Carlos, 2016)
In this thesis, the electronic and structural properties of nanostructured systems were studied aiming to get a realistic model for quantum rings, potentially adaptable for quantum dots. To attain these goals, several studies supported by experimental results were carried out that allowed the introduction to the building blocks for the theoretical models such as: the envelope function approach within the k.p approximation in quantum wells, and quantum ring/dot with perpendicular magnetic field and without spin-orbit interaction. In these models, the effects of size, strain and localization were subsequently introduced to understand the ring formation process and their effects in the photoluminescence and magneto-photoluminescence. The experimental results of atomic force microscopy indicated the importance of structural properties and the types of asymmetries possibly found in quantum rings after the growth process. The understanding of these effects and the evidence of the anisotropy in a preferential direction of the ring helped building more realistic models for the potential profiles. Various systems were then studied with success. They also included a controllably magnetic field (both in magnitude and orientation), beside the geometric deformation, making the ring ellipsoidal, and taking into account the spin-orbit interaction. The most realistic model was used to analyze the Berry phase generation and the relative weight of the contribution of each term of the Hamiltonian.
Keywords: Quantum rings; K.P method; Berry phase; Asymmetry; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA GERAL